2018
DOI: 10.1089/lap.2017.0340
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopy Versus Open Surgery for Persistent Ductus Arteriosus and Vascular Ring Anomaly in Neonates and Infants

Abstract: Our short-term results in thoracoscopic PDA closure and VR anomalies surgery in neonates and infants are comparable to open surgery. Thoracoscopy seems to provide less pain especially for neonates and premature babies and allows to decrease the risk for postoperative chest wall deformities. Long-term outcome is mandatory to confirm these preliminary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Some centers prefer video-assisted thoracoscopic surgery (VATS) division of vascular rings. (18,19) Riggle et al (18) reported that, VAT is a feasible method that can be performed with satisfactory results. They have reduced operative time, decreased ICU admissions, chest tube use, chylothorax and overall short length of stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some centers prefer video-assisted thoracoscopic surgery (VATS) division of vascular rings. (18,19) Riggle et al (18) reported that, VAT is a feasible method that can be performed with satisfactory results. They have reduced operative time, decreased ICU admissions, chest tube use, chylothorax and overall short length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…(20,21) We had experienced one case each with chylothorax, pneumothorax and tracheostomy application owing to extubation failure who had diagnosed with tracheomalacia preoperatively. In the literature, complications rates have a range of (10-27%), (4,6,(16)(17)(18)(19) . However, reported mortality rates are below 1%.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are observational data indicating that open surgery is associated with worsening neurodevelopment of the neonate 18 . In addition, the procedure presents some immediate complications, such as rib fractures, which could be avoided with thoracoscopy 3,14,15 .…”
Section: Thoracotomymentioning
confidence: 99%
“…Although open thoracic surgery is common for PDA ligation or clipping, thoracoscopic PDA closure is an alternative surgical procedure that requires a smaller incision, facilitates postoperative recovery, reduces pain, results in shorter hospital stay, and improves respiratory function. There is also a decrease in the incidence of chest wall deformity in the long term, including scoliosis and breast deformity, leading to better aesthetic results 2,3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation